English Textbook Propriety in Ghana: Examining the Arbitrary Text Appropriation Factor - Bakuuro, Justine; Diedong, Africanus; Tuurosong, Damasus (International Journal of Language Teaching and Education, 2024)
This study sought to examine the suitability of texts in Ghanaian Senior High School English textbooks to their intended students. The textual data was culled from the Global Series English textbook series used in Ghanaian Senior High Schools for the teaching of the English language. Using a descriptive research design, within the constructivist research paradigm, the study revealed that there is gross arbitrary appropriation of texts in Ghanaian English textbooks to the intended learners as the readability levels of the sampled texts were found to be far above the intended grades of the students. Although the study is focused on senior high school, most of the texts (76%) were found to have readability levels suitable for undergraduate and postgraduate learners as they recorded very high (unreadable according to Flesch’s translated index) readability values. Only two percent (2%) of the texts were found to be suitable for their intended grades at the senior high school. The study concludes that readability tests should be conducted on texts in English textbooks before assigning them to students of various grades at the senior high school level in Ghana. KEYWORDS: English Textbook Readability, Grade Propriety, Arbitrary Text Appropriation, Ghana.